Relations between Russia and Lithuania in the contemporary Lithuanian historiography - Nerijus Šepetys (Lietuvos Istorijos Studijos)
It is impossible to imagine the 20th century in the history of Russian and Lithuanian relations without the "Soviet power" brought on the bayonets of the Red Army. Lithuania successfully fended off the bayonets' thrust in 1918-1919; however, these bayonets subdued Lithuania with insidiousness and constraint in 1940 and by force and violence in 1945. But in 1991-1993, these bayonets left Lithuania, taking away the memory of Soviet power.